Prospective cohort study of voice outcomes following secondary tracheoesophageal puncture in gastric pull-up reconstruction after total laryngopharyngoesophagectomy - Emily C. Deane; Harman Parhar; Linda Rammage; Amanda Hu; Donald W. Anderson (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Gastric pull-up is a reconstructive option for circumferential defects after resection of advanced laryngopharyngeal malignancy. Voice loss is expected and vocal rehabilitation remains a challenge. Our study objectives were to investigate the feasibility of secondary tracheoesophageal puncture following gastric pull-up and to analyze voice outcomes. Methods This was a prospective cohort study of patients with advanced laryngopharyngeal malignancies who underwent gastric pull-up and secondary tracheoesophageal puncture between 1988 and 2017 at a tertiary-care academic institution. Objective acoustic measures included fundamental frequency and vocal intensity. Perceptual analysis was performed using voice recordings (“Rainbow Passage”) randomly presented in a blinded fashion to four clinicians using the validated GRBAS scale. Speech intelligibility was assessed in a blinded fashion using a validated 7-point scale. Additionally, the Voice Handicap Index-10 was administered as a validated patient self-reporting tool. Results Ten patients (7 male, 3 female) were included, all of whom preferentially used tracheoesophageal puncture for communication. These patients had abnormal median fundamental frequency of 250 (interquartile range (IQR) 214–265) Hz and a limited median vocal intensity of 65.8 (IQR 64.1–68.3) dB. Perceptual analysis (GRBAS) revealed a median ‘moderate’ degree of impairment [grade 2 (IQR 2–3), roughness 2 (IQR 2–3), breathiness 3 (IQR 2–3), asthenia 2 (IQR 1–2), strain 2 (IQR 1–2)] as did median intelligibility scores [median 5 (IQR 4–7)]. Most patients self-reported an abnormal voice handicap-10 [median 26.5 (IQR 22.8–35.0)]. Conclusion Secondary tracheoesophageal puncture is a safe and feasible option for voice rehabilitation after gastric pull-up. Although analyses demonstrated moderate subjective and objective impairment, tracheoesophageal puncture provided patients with a self-reported means of functional verbal communication and was their preferred method of communication. Graphical abstract